Analytical solution on performance of unsteady casson fluid with thermal radiation and chemical reaction - Nur Fatihah, Mod Omar; Husna Izzati, Osman; Ahmad Qushairi, Mohamad; Rahimah, Jusoh; Zulkhibri, Ismail (Semarak Ilmu Publishing, 2022)
Casson fluid is classified as the non-Newtonian fluid and has a prominent application in the medical and engineering sector due to its elasticity behaviour. This study provides the analytical solution on performance of unsteady Casson fluid with the inclusion of thermal radiation and chemical reaction. Formulation of this fluid model is initiated with the partial differential equation (PDE) ofthe momentum and energy equations as well as the concentration equation. By applying the proper non-dimensional variables, these equations are then converted into dimensionless form. Subsequently, the derivation of the exact solutions for the temperature and velocity profiles is conducted with the utilisation of the Laplace transform method that satisfies both initial and boundary equations. Graphical illustrations, which portray the effects of the thermal radiation and chemical reaction are generated. It has been discovered that as the temperature rises, so does the thermal radiation. Additionally, when the value of the chemical reaction parameter increases, the concentration drops.